Properties of phase-shifting devices used in researches of nonlinear absorption - Kulish, M.R.; Malysh, N.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
. Formulated in this work are the requirements to the Fresnel rhomb used for
light polarization control of high-power lasers. Technical parameters of the rhomb have
been given. The calibration procedure of the Fresnel rhomb has been described. The
single rhomb is proposed to be utillized for the change of light ellipticity from zero to
unity, and block of two rhombi for the turn of polarization plane between zero to 360
degrees.